Revisited Vanoni-Brooks sidewall correction - Cheng, Nian-Sheng (2012)
The evaluation of the sidewall friction could be inconvenient in the implement of the Vanoni-Brooks sidewall correction procedure. Using the Colebrook-White equation and Nikuradse's pipe friction data, two explicit formulae are developed in this note for finding the sidewall friction factor. They are applicable for various sidewalls that are either hydrodynamically-smooth or rough, or in the transitional regime.